Iklim Organisasi dan Kepuasan Kerja Sebagai Strategi Mempertahankan Karyawan: Studi Pada Perusahaan Dealer Mobil Pekanbaru - Kasmiruddin Kasmiruddin; Ruzikna Ruzikna; Lie Othman; Nurjanah Nurjanah (Jurnal Administrasi Bisnis, 2021)
The desire to leave the company or called turnover intention will interfere with organizational performance in realizing the company's goals to win business competition. Turnover intention is likened to a disease that is difficult to cure by a company so that it becomes a challenge for companies to try to retain experienced employees. It is important for leaders to create an organizational climate and employee job satisfaction so that it can be a strategy for maintaining employee presence in the company. This study aims to analyze the influence of organizational climate and job satisfaction on the desire to leave the company. The population or research object is one of the dealer companies that are experienced in the city of Pekanbaru, namely Truck Car Dealers. Data collection using a questionnaire, and data analysis using SmartPLS 2.0 analysis. The results showed that the coefficient of determination (R2) for the variable willingness to leave was 0.589. This means that the output desire construct variable can be explained by the variability of organizational climate and job satisfaction of 58.90% while the remaining 41.10% is explained by other variables outside the research model. It is proven that there is a significant influence of organizational climate on the desire to leave the company and job satisfaction on the desire to leave the company. Recommendations that it is important for company leaders to improve the quality of the organizational climate by providing better work facilities and employee job satisfaction through increasing the provision of more attractive incentives or bonuses.Penelitian ini bertujuan untuk menganalisis apakah iklim organisasi dan kepuasan kerja berpengaruh signifikan terhadap keinginan keluar karyawan, dan menentukan apakah iklim organisasi dan kepuasan kerja efektif sebagai strategi mempertahankan karyawan pada Perusahaan Dealer Mobil di Pekanbaru. Metode penelitian yang digunakan metode kuantitatif dengan tipe penelitian eksplanatori, dan menggunakan data primer yang diperoleh dari responden. Data dikumpulkan melalui kuesioner yang terdiri dari 32 pertanyaan; Sampel terdiri dari 100 responden karyawan dari populasi sebesar 118 karyawan dengan menggunakan teknik purposive smpling. Data yang dikumpulkan dari kuesioner menggunakan pengukuran skala likert dan pengolahan data menggunakan statistik regresi liner berganda melalui SPSS versi 22.0. Temuan hasil penelitian: 1) iklim organisasi dan kepuasan kerja berpengaruh signifikan negatif terhadap keinginan karyawan keluar dari perusahaan; 2)Ikllim organisasi tidak berpengaruh signifikan negatif terhadap keinginan karyawan keluar dari perusahaan; 3)kepuasan kerja memiliki pengaruh signifikan terhadap keinginan karyawan keluar perusahaan. Implikasi hasil penelitian, iklim organisasi dan kepuasan kerja sebagai strategi mempertahankan karyawan sudah tepat secara kolaborasi, tapi tidak efektif sebagai strategi tunggal.